2019
DOI: 10.3346/jkms.2019.34.e116
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Prediction Score for Community-Onset Bloodstream Infections Caused by Extended-Spectrum Beta-Lactamase-Producing Escherichia coli and Klebsiella Species

Abstract: Background This study aimed to identify the predictors and build a prediction score for community-onset bloodstream infections (CO-BSIs) caused by extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli and Klebsiella species. Methods All CO-BSIs caused by E. coli and Klebsiella species from 2012 to 2015 were grouped into derivation (BSIs from 2012 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
9
1
Order By: Relevance
“…The resistance rates of E. coli and K. pneumoniae to 3GCs and FQs were much higher in the Korean Anti-microbial Resistance Monitoring System (KARMS) from 2013 to 2015 than in our study because KARMS data includes both nosocomial and community pathogens [ 7 ]. In a recent study of community-onset E. coli and Klebsiella species bacteremia from 2012 to 2015, 27.2% of E. coli and 14.9% of Klebsiella species were ESBL producers and the ciprofloxacin resistance rate was 38.7% in E. coli and 21.0% in Klebsiella species [ 2 ]; the resistant rates of 3GC and FQs were higher than reported in our studies, especially in the Klebsiella species , because the underlying comorbidities were more severe than those of our studies. Because Daegu Fatima Hospital is a secondary care community-based medical institution, we believe that our data reflects the antimicrobial resistance rates in community-onset infections, and therefore, 3GCs and FQs remain useful empirical options for community- onset infections caused by K. pneumoniae .…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…The resistance rates of E. coli and K. pneumoniae to 3GCs and FQs were much higher in the Korean Anti-microbial Resistance Monitoring System (KARMS) from 2013 to 2015 than in our study because KARMS data includes both nosocomial and community pathogens [ 7 ]. In a recent study of community-onset E. coli and Klebsiella species bacteremia from 2012 to 2015, 27.2% of E. coli and 14.9% of Klebsiella species were ESBL producers and the ciprofloxacin resistance rate was 38.7% in E. coli and 21.0% in Klebsiella species [ 2 ]; the resistant rates of 3GC and FQs were higher than reported in our studies, especially in the Klebsiella species , because the underlying comorbidities were more severe than those of our studies. Because Daegu Fatima Hospital is a secondary care community-based medical institution, we believe that our data reflects the antimicrobial resistance rates in community-onset infections, and therefore, 3GCs and FQs remain useful empirical options for community- onset infections caused by K. pneumoniae .…”
Section: Discussioncontrasting
confidence: 63%
“…Nevertheless, our hospital is the largest secondary care medical institution in the Daegu area and we analyzed more than one thousand cases of E. coli and K. pneumoniae community-onset bacteremia. In our study, the proportion of patients with underlying comorbidities was lower than a community-onset bacteremia study conducted at a tertiary care hospital in Seoul [ 2 ]. Therefore, we believe that our data are more representative of community-onset infections than those of studies performed in a tertiary care hospital.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Several studies have reported risk factors associated with ESBL production [4], but fewer studies have focused strictly on community-onset risk factors. The most consistent communityonset risk factors include previous use of (specific) antibiotics [5e13], recent hospitalization [5,7,8], health-care-associated infection [9,11,13], urological disease [6,8,9] and urinary catheter use [5,7,11]. Still, the majority of these studies have been from high prevalence areas, they were of limited size, and only one [6] was population-based.…”
Section: Introductionmentioning
confidence: 99%
“…ESBL-PE hydrolysis of carbapenem antibiotics is low, so carbapenem antibiotics are often used as the rst choice in clinical treatment of ESBL-PE infections. However, the abuse of carbapenems may result in the selection of carbapenem resistant Enterobacteriaceae, which will ultimately make it more di cult to treat this kind of bacteria [3,4].…”
Section: Introductionmentioning
confidence: 99%